KINERJA PEGAWAI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK (STUDI KASUS PELAYANAN KARTU TANDA PENDUDUK DAN KARTU KELUARGA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN ROKAN HULU) - Alirman, Novrilla; Harahap, Tuti Khairani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Administration has elements wich are officialdom or appratus. To crry out it duties ang functions as the state apparatus in the administrasion of the need for human resource management. Human resource managemen are the state performance assesment of the state apparatus in craying out it duties and fungctions as public servants including the admnistrasion of residence. Administrative service residence especiallyresidents card and family card are important thing, it due to this Ministry in contact directly with the community. The large number of complaints that are submitted by users of this service, resulting in poor Imaging for a given instance of the authority in providing the service of Residents card and family card for the community, they isDinas Kependudukan dan Pencatatan Sipil Rokan Hulu.The concept of theory used is performance, raised by Kumorotomo in Harbani Pasolong with four indicators, they are efficiency, effectiveness, fairness and responsiveness. The purpose of this research is to find out how the effectiveness the service of Dinas Kependudukan dan Pencatatan Sipil Rokan Hulu in providing service to make residents card and family card to the people who need this service. This research uses qualitative study with data in dekskriptif. In the data collection the author uses interviews technique and observations. The author uses the informant as a source of information the triangulationtechnique as the source of the validity of the data.The results of this research show that the service of making residents card and family card are already effective but still encountered constraints like a poorinfrastructure and lack of responsiveness employees. Factors that influence the effectiveness of employee performance in improving the quality of public service in Dinas Kependudukan dan Pencatatan Sipil Rokan Hulu is the infrastructure, human resources and public awareness.Key word: human resource management,performance, public service.